2019
DOI: 10.1016/j.smrv.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The psychological wellbeing outcomes of nonpharmacological interventions for older persons with insomnia symptoms: A systematic review and meta-analysis

Abstract: M (2019) The psychological wellbeing outcomes of nonpharmacological interventions for older persons with insomnia symptoms: a systematic review and meta-analysis. Sleep Medicine Reviews, 43. pp. 1-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Non-pharmacological approaches have shown success among older adults and include: cognitivebehavioral therapies (CBT) for anxiety, insomnia, and/or pain; mindfulness; acupuncture; and physical therapy options. 14,18,19,[36][37][38] In the PCP environment, however, multisession interventions have lacked practicality because of time and resource limitations. In addition, many published interventions remain within research settings, involve small study samples, and consequently have not been widely implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological approaches have shown success among older adults and include: cognitivebehavioral therapies (CBT) for anxiety, insomnia, and/or pain; mindfulness; acupuncture; and physical therapy options. 14,18,19,[36][37][38] In the PCP environment, however, multisession interventions have lacked practicality because of time and resource limitations. In addition, many published interventions remain within research settings, involve small study samples, and consequently have not been widely implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguing were nonetheless the results of a small study that utilized experience sampling methods and revealed associations between a real-time objective air pollution index (derived from hourly real-time data released by the Beijing Environmental Protection Bureau) and in-time ratings of subjective wellbeing (negative association with affective ratings) and eudaimonic wellbeing (positive association with ratings of meaning and purpose in life) [34]. Both physical (in) activity and sleep covaried with ratings of psychological wellbeing and distress, and both behaviors were linked with risk of mental health disorders such as depression [35][36][37][38][39]. To what extent this "protection" is maintained when PA is performed in air polluted environments requires further study.…”
Section: Air Pollution and Mental Healthmentioning
confidence: 99%
“…Many studies have proven that adolescents and their parents favor psychotherapy over pharmacotherapy [31], and cognitive behavioral therapy for insomnia (CBT-I) appears to be superior to hypnotics in the long run [32]. Metaanalysis has already supported that treating insomnia via CBT-I in both adults and elderly with depression has a positive effect on depressive symptoms [33,34]. To date, the literature has not been sys-tematically reviewed to evaluate the role of CBT-I in adolescents with comorbid insomnia and depressive symptoms.…”
Section: Insomnia and Depressive Symptoms: Shares The Common Charactementioning
confidence: 99%